Climate and culture Changes, lessons, and challenges - Winarto, Yunita T. (UI Scholars Hub, 2010)
From generation to generation over the centuries, people in all parts of the world have developed adaptive social-cultural institutions and strategies of natural resource management based on the intimate relationship they had with their environment. At present, recent global warming is threatening people's lives. Unfortunately, climate change is a natural phenomenon which is neither easy to observe, nor to predict and anticipate accurately. In many places, local people can no longer rely on earlier experiences and existing socio-cultural institutions to adjust to unprecedented changes. We are in urgent need of specific efforts to re-interpret and enrich our knowledge of this natural phenomenon. However, this is not an easy thing to do. People from all kinds of levels and entities in society are simultaneously the cause and the victims of global warming. The problem becomes even more complicated because of various mutually-affecting dimensions like ethics, politics, power, economics, and justice. These are the ultimate challenges scholars of the social sciences and humanities need to address seriously everywhere in the world, including in Indonesia. This article addresses the arguments of what scholars in the social sciences and humanities could and should do in response to climate change. Promoting a new paradigm and ethics in dealing with climate change is urgent and improvements in approaches and research methodologies are necessary. Learning from experiences gained from the way farmers in Java respond to climate change, the author argues that interdisciplinary research across social and natural sciences, and collaborative work with target groups is a promising and significant step (although scholars will have to face many challenges and constraints).